Pengelolaan Risiko berbasis Nilai Catur Purusa Artha terhadap Kinerja Keuangan BUMDes - Ni Luh De Erik Trisnawati (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to examine the effect liquidity risk, credit risk and financial performance, through the application of the catur purusa artha concept as a basis for risk management, at BUMDes Dwi Tunggal, Buleleng Regency. This research use multiple linear regression method. The results of this study indicate that Liquidity risk have a significant effect on financial Performance. Credit risk has no significant effect on financial performance. The value of chess purusa artha with dharma as the basis for risk management encourages BUMDes managers to have the same commitment in building risk control awareness. This strategy ultimately reduces credit risk, which results in a decrease in NPL and maintains liquidity risk.